Mindfulness acting with awareness and emotional eating among polycystic ovary syndrome women with infertility: the mediating role of depression - Yang, Mengye; Wang, Xiaoyu; Zhang, Yan; Qian, Weina; Tang, Yan (Frontiers in Psychology, 2024)
Emotional eating, characterized by the tendency to increase food intake in response to negative emotional states, is often linked to poor emotion regulation. While mindfulness-based interventions have been studied for their benefits in reducing emotional eating, less is known about how inherent mindfulness traits, relate to emotional regulation particularly among individuals with polycystic ovary syndrome (PCOS), a population known for high rates of psychological distress and disordered eating behaviors. This study investigates the associations between different facets of mindfulness, depressive symptoms, and emotional eating among individuals with PCOS and infertility who had not received any formal mindfulness intervention. A cross-sectional study was conducted involving 334 individuals. Participants completed the Five Facet Mindfulness Questionnaire-Short Form (FFMQ-SF), the Patient Health Questionnaire (PHQ-9) to assess depressive symptoms, and the Dutch Eating Behavior Questionnaire (DEBQ) to measure emotional eating. Structural Equation Modeling (SEM) was employed to examine the relationships between inherent mindfulness traits (i.e., observation, describing, acting with awareness, non-reactivity, and non-judgment), depressive symptoms, anxiety, and emotional eating. The findings indicated that the trait of acting with awareness may reduce emotional eating through its influence on depressive symptoms, while observational mindfulness was found to be associated with increased emotional eating without prior external mindfulness training. In conclusion, Mindfulness is a multidimensional construct, with its facets contributing differently to emotional regulation and eating behaviors in individuals with PCOS and infertility.Future research should explore these nuances to develop more targeted interventions.